Perceived sexual harasment as a function of locus of control and other personal characteristics (1999)
The perception of sexual harasment as a function of locus control and personality characteristics was investigated using 200 female and male respondents who were randomly selected among university students, secondary school teachers and bank workers with a mean age of 22.97 years. they were administered the self esteem scale, locus of control scale and perceived sexual harasment scale that was purposely developed for this research. It was observed that age, locus of control and sex have an interactional influence in the perception of sexual harasment (R2= 0.14, p<. 001), married people have a higher perception of sexual harasment than single people (t=4.5, p<.05), but no significant difference difference between students and workers in their perception of sexual harasment. The findings were discussed in line with the Riger's (1991) theory of attribution. The implication of the findings for legal interpretation of sexual harasment and psychological dynamics involved were highlighted